2014
DOI: 10.1053/j.gastro.2014.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Alkaline Phosphatase and Bilirubin Are Surrogate End Points of Outcomes of Patients With Primary Biliary Cirrhosis: An International Follow-up Study

Abstract: Levels of alkaline phosphatase and bilirubin can predict outcomes (liver transplantation or death) of patients with PBC and might be used as surrogate end points in therapy trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
347
2
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 401 publications
(385 citation statements)
references
References 33 publications
15
347
2
12
Order By: Relevance
“…1 The question of whether reduction in ALP levels is sufficient to predict transplant-free survival is highly pertinent to therapeutic trials and currently being assessed using a cohort of 3895 PBC patients. 3 Our group has isolated a human beta-retrovirus from patients with PBC and recently reported that the major- ity of PBC patients have evidence of retroviral integration in their biliary epithelial cells. 4,5 To find new therapeutic avenues and link viral infection with PBC, we have conducted pilot anti-retroviral studies.…”
mentioning
confidence: 99%
“…1 The question of whether reduction in ALP levels is sufficient to predict transplant-free survival is highly pertinent to therapeutic trials and currently being assessed using a cohort of 3895 PBC patients. 3 Our group has isolated a human beta-retrovirus from patients with PBC and recently reported that the major- ity of PBC patients have evidence of retroviral integration in their biliary epithelial cells. 4,5 To find new therapeutic avenues and link viral infection with PBC, we have conducted pilot anti-retroviral studies.…”
mentioning
confidence: 99%
“…More recently, a pooled metaanalysis by the Global PBC Study Group included data from 15 cohort studies and a total of 4845 patients, of whom 1118 reached a clinical endpoint. This metaanalysis showed excellent correlation between serum ALP and bilirubin and survival free of LT (156) . The greater the reduction in serum ALP levels after 1 year of treatment with UDCA, the better the transplantfree survival.…”
mentioning
confidence: 64%
“…Typically, an early significant drop is noted in serum ALP, followed by a progressive, slow, continued drop. To date, several sets of criteria have been developed by mul tiple investigators to assess biochemical response to UDCA and predict longterm outcomes, described in Figure 2 (155,156) . More recently, a pooled metaanalysis by the Global PBC Study Group included data from 15 cohort studies and a total of 4845 patients, of whom 1118 reached a clinical endpoint.…”
mentioning
confidence: 99%
“…Reig et al showed that aft er a median treatment duration of 37.9 months, just over half of study subjects completely normalized serum ALP, a major predictor of outcomes in this population ( 6 ). Indeed, all fi ve cases of progression to death ( n =1), liver transplant ( n =3) or hepatocellular carcinoma ( n =1) occurred among non-responders to bezafi brate, that is, patients who did not normalize ALP while on treatment.…”
mentioning
confidence: 97%